2001
DOI: 10.1016/s1359-6454(01)00294-4
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of open-cell aluminum foam

Abstract: Abstract-The mechanical properties of high-purity aluminum foams produced by replication from salt precursors are measured in compression. These foams have homogeneous open-porosity, cell sizes equivalent to the particle size of the precursor salt (ෂ500 µm in this case) and relative densities near 25%. Deformation is uniform and strain hardening similar to the bulk material is observed without a plateau stress. A simple analytical model based on beam theory is employed to describe the flow stress and the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(118 citation statements)
references
References 45 publications
(64 reference statements)
11
106
0
1
Order By: Relevance
“…1d). Similar structures have been observed in other metal foams prepared by this method [28][29][30]. As indicated in Fig.…”
Section: Resultssupporting
confidence: 87%
“…1d). Similar structures have been observed in other metal foams prepared by this method [28][29][30]. As indicated in Fig.…”
Section: Resultssupporting
confidence: 87%
“…Details of the process and the structure of replicated aluminum foams can be found in [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…The density of the foams was measured from the mass knowing the dimensions of machined test specimens. The salt used in this study is the same as in [19], namely high-purity, spheroidal NaCl particles of an average diameter of 400 lm. All test specimens were machined from the NaCl-Al composite castings prior to removal of the salt.…”
Section: Methodsmentioning
confidence: 99%
“…They can amongst others be used as catalyst support [1,2], implant material [3], heat exchanger [4], sound absorber [5] and energy/impact absorbers [6,7,8,9,10,11,12,13]. In the future OCMFs may have the potential to partially replace the relatively heavy bulk metals used in crumple zones of cars as low-weight energy absorbers [14].…”
Section: Introductionmentioning
confidence: 99%
“…PtFeAlO, NiTi, Ta) [1,3,16]. This study focuses on those made of aluminium (Al) [6,9,10,11,12,13,14,15]. Jung et al have shown that the energy-absorbing characteristics of OCAFs can be greatly enhanced by coating them with nickel (Ni) [11,12,13,15].…”
Section: Introductionmentioning
confidence: 99%